The Kings and Wisdoms in Surakarta and Yogyakarta Folktales - Eko Wardani, Nugraheni (KnE Social Sciences, 2023)
This research aimed to explain the king’s character and the wisdom in Surakarta and Yogyakarta folktales. The results showed that the king of Kanjeng Sinuhun, Paku Buwono, was the main character in the Surakarta folktale. The king, Sri Sultan Hamengkubuwono, is also the main character in the Yogyakarta folktale. Folktales use the king as the main character who is a patron of the people. The king is the master of a microcosm who tries to unite the microcosm and the macrocosm so that they exist in harmony. Wisdom in the Surakarta and Yogyakarta folktales consists of wenang wisesa ing sanagari (having the highest authority in the country), gung binathara bau dhendha nyakrawati (having as much as the power of God, being the keeper of the law and the ruler of the world), and berbudi bawa leksana ambeg adil paramarta (having a fair and wise leadership). Keywords: Kings, Local Wisdom, Folktale